RegTech and Accounting of Financial Institutions Under Financial Inclusion: Conceptual Framework Analysis - Dabour, Israa (International Journal of Accounting and Financial Reporting, 2023)
The paper aims to analyze the expected impact of regulatory technology (RegTech) on the development of the accounting of financial institutions under financial inclusion. The nature of the work of financial institutions differs from the nature and laws of work and accounting in other commercial companies. Here comes the role of accounting to accommodate the surrounding variables in business environments and to work on the development of accounting practice in order to reach sound outputs for information users and then rationalize decisions that have an impact on the financial markets. Therefore, the paper concludes that the efforts of the professional and concerned authorities must be combined with regard to the development of accounting standards that are appropriate with the nature and work of financial institutions in order to accommodate the constantly developing technological factors within the sector due to the decrease in professional efforts about accounting in digital financial institutions.